EDUKASI PENCEGAHAN STUNTING PADA IBU-IBU DUSUN TELAGA PANGE - Nana Ronawan Rambe; Laila Sahubauwa; Heni Mutmainnah; Corneli Pary; Janaba Renngiwur (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Stunting is a serious threat to the quality of Indonesian people, including the nation's competitiveness. Because stunted children are not only disrupted by their physical growth (small/dwarf size), but also by disrupted brain development, which of course greatly affects their abilities and achievements in school, productivity and creativity in productivity. The purpose of this activity is to provide public knowledge and awareness regarding stunting and the application of balanced nutrition, nutritious food innovation training for stunting prevention. The method in this activity is the mentoring method which is a combination of counseling, training¸ demonstrations and practice. The material was presented using powerpoint to the community (mothers in Telaga Pange Hamlet, Rumah Tiga Village, Ambon City) who were the target audience. There were 30 participants who took part in the activity. The results of stunting prevention education show an increase in public knowledge and awareness regarding stunting and the implementation of balanced nutrition in Telaga Pange Hamlet, Rumah Tiga Village, Ambon City. This can be seen from the participants' responses during the question and answer session and evaluation. The community is very skilled and enthusiastic in demonstrating or practicing making Moringa leaf ice cream and fruit satay.